Facilitators of E - Tail Patronage Behavior Among Generation Z Consumers - Mishra, Vivek; Das, Biswajit (Indian Journal of Marketing, 2019)
Online retail (e-tail) has evidently been growing at a fast pace owing to the humongous degree of online purchases by individuals. However, due to a complex market scenario, intense competition, and ever-changing consumer dynamics, sustainability is skeptical. Hence, online retailers are extremely focused on the loyalty aspect of buyers. In the context of the same, it is pivotal for marketers to identify those factors that foster e-tail patronage behavior amongst online buyers. According to the National Statistical Survey, more than 50% of India's population is below the age of 25 years. Therefore, this study was designed to specifically examine the e-patronage behavior of generation Z, who form the core of India's population. The objective of this research was to explore those factors of an e-tail store that are pivotal in developing a sense of loyalty among online shoppers. Steered by the stimulus - organism - response model and existing literature, this paper investigated e-tail patronage behavior of generation Z consumers by emphasizing on three variables, namely; e-tail store atmospherics, e-tail service quality, and merchandise & patronage intentions. Survey data were collected through a self-administered questionnaire from a total of 371 respondents. The responses were analyzed using SPSS package 20.0. The results depicted nine prominent factors, which facilitate e-tail patronage. A significant correlation between the same and criterion variable was also revealed. The outcomes further revealed that e-merchandise elements were negatively associated with e-patronage intentions ; rather, e-service quality and e-tail atmospheric components positively predicted consumer e-patronage.